The Impact of Using Audio Visual as a Vocabulary Learning Tool toward UNCP Students Proficiency - Juwita Crestiani M; Opik Dwi Indah; Hermini Hermini (Institut Agama Islam Negeri Palopo, 2023)
This research deals with analysis of the impact of using audio visual as a vocabulary learning tool toward uncp students proficiency. The population of this research was the sixth semester students of Primary School Teacher Education Study Program of Palopo Cokroaminoto University in academic year 2022/2023. The total number of population was 200 students. The researcher applied the purposive sampling technique because the sample still very poor in vocabulary. Vocabulary test is the instrument of this research. Based on the findings and discussion in the previous chapter, the researcher concludes using audio visual as a vocabulary learning tool toward uncp students’ proficiency has impact. It can be proven by the students’ mean score in post test 85.2 was higher (good) than the students’ mean score in pre test 43 (very poor).